ScalabletTest Framework for device driver validation - Nagabhushan Reddy, P.; T. Bhaskara Reddy, Dr. (International Journal of Engineering and Technology, 2019)
Real-time embedded systems are increasingly being implemented on system-on-chip (SoC) devices in order to take advantage of lower power consumption, lower unit cost, and higher integration. These SoCs have processors, memory, peripherals, controllers, and other subsystems on the same silicon die. Based on the different business requirements wide variety of SoCs are designed and manufactured.The application development on these SoCs requires device drivers for communicating with the peripherals. Some of the most common device driver categories are: Serial (I2C, SPI, UART), Storage (MMC/SD, NAND etc), Audio, Connectivity (USB), Networking and Video. The interfaces and implementation of these device drivers vary with different SoCs and RTOS (e.g. DSP/BIOS, PrOSetc).With increasing number of SoCs and less time to market, the device driver validation needs to be efficient and reliable. Typically test benches or test suites are developed to carry out the validation. Such test benches should have an architecture that helps plugging in new testcases easily, provide test case portability across SoCs and RTOS, enable ease of use, help in regression tests, provide better maintainability and improved time to market.The purpose of this paper is to explain the architecture of the test bench that we have developed. We also want to share the details on prior work/experience, what motivated us to develop the test bench. We will also cover the impact of these test benches across different teams within our organization and our customers. Finally we will conclude with the status of current work and future plans.Â Â